Indonesia Economic Quarterly, March 2018 : Towards Inclusive Growth - World Bank (World Bank, Washington, DC, 2018)
Real GDP growth picked up to 5.2 percent yoy in Q4 from 5.1 percent in Q3, driven by higher domestic demand, in particular stronger investment. Private consumption growth also strengthened marginally, partly due to consumer price inflation easing in Q4. Export and import growth moderated from a peak in Q3 and remained robust due to a sustained recovery in global trade and commodity prices. Net exports, however, were a drag on growth in Q4, partly reflecting higher investment in machines and equipment and associated imports of capital goods. After significant destocking in Q3, inventories contributed positively to GDP growth. On the production side, growth in manufacturing accelerated, while construction and otherservices sectors saw the fastest growth.